Accumulative fusion and the issue of age: Reconciling the model with the data. (27th December 2018) - Rosenzweig, Cheskie; Ruisch, Benjamin C.; Stern, Chadly
Abstract: We discuss a disconnect between the predictions of Whitehouse's model regarding the accumulative nature of fusion and real-world data regarding the age at which people generally engage in self-sacrifice. We argue that incorporating the link between age and identity development into Whitehouse's theoretical framework is central to understanding when and why people engage in self-sacrifice on behalf of the group.